Pentaploid Wheat Hybrids: Applications, Characterisation, and Challenges - Padmanaban, Sriram; Zhang, Peng; Hare, Ray A.; Sutherland, Mark W.; Martin, Anke (Frontiers in Plant Science, 2017)
Interspecific hybridisation between hexaploid and tetraploid wheat species leads to the development of F1 pentaploid hybrids with unique chromosomal constitutions. Pentaploid hybrids derived from bread wheat (Triticum aestivum L.) and durum wheat (Triticum turgidum spp. durum Desf.) crosses can improve the genetic background of either parent by transferring traits of interest. The genetic variability derived from bread and durum wheat and transferred into pentaploid hybrids has the potential to improve disease resistance, abiotic tolerance, and grain quality, and to enhance agronomic characters. Nonetheless, pentaploid wheat hybrids have not been fully exploited in breeding programs aimed at improving crops. There are several potential barriers for efficient pentaploid wheat production, such as low pollen compatibility, poor seed set, failed seedling establishment, and frequent sterility in F1 hybrids. However, most of the barriers can be overcome by careful selection of the parental genotypes and by employing the higher ploidy level genotype as the maternal parent. In this review, we summarize the current research on pentaploid wheat hybrids and analyze the advantages and pitfalls of current methods used to assess pentaploid-derived lines. Furthermore, we discuss current and potential applications in commercial breeding programs and future directions for research into pentaploid wheat.